Brief survey of meiji slogan (fukoku kyohei) and its influence on the modernization of Japan in the 19th century - Mansor Majdin, Mohamad Firdaus (Asian Scholars Network, 2020)
This article analyses the acceptance of Fukoku Kyohei slogan (which means a strong and prosperous nation) amongst the Japanese statesmen in the early and late Meiji periods. This ideology connotes a sort of agenda in transforming the Japanese state into a prosperous nation, strong army. This was evidently felt at least during the last years of Shogunate administration as well in the early foundation of Meiji government since 1868 onwards. Retrospectively, the Japanese leaders found this ideology timely as they were aware of increasing Western presence in the East Asian region. The study demonstrates that some of Japanese leaders (Ito Hirobumi, Saigo Takamori and Kido Takayoshi to name a few) whom later had paved the way for Meiji Restoration in 1868, realized the necessity for Japan to transform itself into a modernized nation in order to contain the ever increasing Western encroachment into their country that would safeguard the sovereignty of Japan. This was realized undeniably by putting an end to the Bakufu administration in the hands of Meiji reform-minded leadership key which paved the way for the creation of modern administrative, political and economic changes in Japan as early as 1870s. Finally, it also analyses the attitude of the some Meiji key figures towards the issue of modernization in Japan who were found to be divided in their views and approaches towards achieving and realizing this modernization agenda in Japan. In doing so, this study adopts the method of content analysis by scrutinizing the scholarly works written by the Japanese scholars and Western writers alike on the topic under study.